Pengaruh Lama Pemakaian Minyak Shell Diala B Terhadap Kuat Tegangan Tembus - Aulidina Dwi Nur Andriyanti (Jurnal Mosfet, 2025)
The electrical energy distribution of the power plant to customers was required the role of transformer that could increase and decrease voltage levels. Transformers was essential equipment in electricity distribution, both in transmission and distribution systems. Transformer was arranged of conductive materials and operated continuously, therefore it was need to be protected by insulation. The liquid insulation was commonly used, such as Shell Diala B which focused on this research. Although insulating oil was able to use over a long period, it might be regularly monitored because its ability to protect electrical equipment deteriorate. This paper was used laboratory research as the method. The researcher analyzed the effect of usage duration to determine its dielectric breakdown strength. It was found that the longer Shell Diala B oil is used, the more its quality declines, indicated by increased turbidity and decreased dielectric performance.